Pour une esquisse biogéographique du Saint-Laurent - Rousseau, Jacques (Cahiers de géographie du Québec)

(untitled) (Département de géographie de l'Université Laval, 1967)
In most instances, biogeographical monographs deal only with a fragmentary aspect of the subject-matter. In spite of their titles, some of these monographs are nothing but phytogeographical essays, and even then, these deal with a limited range of phanerogams only and leave aside the cryptogams. This is so because the authors, when they are not also systematically oriented, neglect a large segment of the flora and fauna. Research conditions also require sometimes specialization around one particular point. A biogeographical study which would claim to be comprehensive must include not only the vegetation cover, the fauna, and man in his many-sided activities, but also a description of the whole living world since the very beginnings of the organization of the Biosphere.Taking the Saint-Lawrence River, this essay depicts some examples of features which are all-important in an unabridged biogeography. Thus, the study deals successively with the pageant of life on the River since the Precambrian era ; a brief look at the discordant levels of the Laurentian flora : the upper part of the thalweg, the banks, the shores, and the waters, since each of these elements follow a different evolution in their rhythm; the calendar of the seasons and the irregularities which upset the climatic cycle. Finally, man enters the scène with all the elements which tie him to the River: patterns of settlement, toponymy, house construction styles, clothing, transportation, gathering, hunting, forestry and agriculture, gastronomy, medicine, and, finally, the role of the River in recreational activities and in literary works.Since the author bas devoted nearly half a century to the study of the River, this essay sometimes includes autobiographical elements.